Eksperimentasi Pembelajaran Matematika Dengan Tipe Two Stay Two Stray, Numbered Heads Together, Dan Think Pair Share Ditinjau Dari Kreativitas Terhadap Hasil Belajar Siswa Kelas VIII SMP Negeri 6 Sukoharjo - , Sugiyamti, Prof. Dr. Sutama. M.Pd, Dr. Suyatmin. M.Si (2017)
This research was conducted with the following objectives: (1) To examine differences in learning outcomes of a thematics in terms of a cooperative strategy type Two Stay Two Stray (TSTS), Numbered Heads Together (NHT), or Think Pair Share (TPS), (2) to analyze changes learning of mathematics in terms of increased activity, (3) analyzing the interactions of learning in terms of student creativity with the type cooperative strategy Two Stay Two Stray (TSTS), Numbered Heads Together (NHT), or Think Pair Share (TPS). The research including the Experimental Design Quasi-Static Group Comparison. Place of research carried out in SMP Negeri 6 Sukoharjo, Central Java Province. Research was conducted in the first semester of the academic year 2016/2017. The conclusion of the study is (1) There are differences in the results of learning mathematics in terms of cooperative learning model Two Stay Two Stray (TSTS), Numbered Heads Together (NHT), or Think Pair Share (TPS) with each value is significantly smaller than 0, 05. Hypothesis is proved, (2) There are interactions of learning in terms of creativity of students with cooperative learning model Two Stay Two Stray (TSTS), Numbered Heads Together (NHT), or Think Pair Share (TPS) with each value nificantly smaller of 0.05. The hypothesis is proven, (3) There is a change in the learning of mathematics in terms of the progress of the activity with the differences in average value at each learning of mathematics. Hypothesis is proved.